Pengaruh Metode Drill Terhadap Hasil Pukulan Forehand Overhead Lob Bulutangkis Ekstrakurikuler Siswa SMPN 3 Babakancikao - Hanif, Abdul Fattah; Nasution, Nana Suryana; Nurwansyah, Rhama (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2023)
The purpose of this study was to find out how much influence the drill method had on the results of extracurricular forehand overhead lob badminton strokes for students at SMPN 3 Babakancikao. This study uses a quantitative approach with experimental research methods. This research was conducted at SMPN 3 Babakancikao from 10 May to 5 June 2023. The study population consisted of 20 extracurricular students at SMPN 3 Babakancikao. The population in the study was taken using a saturated sampling technique, a sample of 20 people consisting of 12 boys and 8 girls. The data collection technique used the pretest and posttest techniques, while the data analysis used the t test. Based on the output results using SPSS 25, the average value before being given the drill method was 58.00, after being given treatment with the drill method it was 80.90. In conclusion, learning the badminton forehand overhead lob technique using the drill training method can improve the results of extracurricular students' badminton forehand overhead lob skill tests. Keywords: drill method, forehand overhead lob, badminton, extracurricular